Konseling Kelompok Untuk Meningkatkan Self Control pada PTRM (Program Terapi Rumatan Metadon) - Wahyu Utami (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2016)
The subject in this case is seven male PTRM in Malang. Assessment methods used are observation, interviews and the scale of self control. The assessment results show that the last four months of oral methadone dose increased. This is because there are some problems they face, one of which patients had resistance from the surrounding environment and the core environment, so they are more convenient to gather the community related to a drug that causes them difficult to break away from drugs. Interventions using counseling group consists of 6 sessions, which aims to improve the self-control to not use drugs. The results of the intervention showed that subjects were able to control myself not to use drugs, the subject also has a reason to reject the anticipation at the time was in a group of drug users